When South Meets South: A Case of African-Philippines Treaty Relations - Sinco, Noel (Social Sciences and Development Review, 2024)
The African-Philippines Relations connected through the manifestation of bilateral agreements with the respective African States with Egypt obtaining the most of it. The World Bank (2023) established the Small States Forum (SSF) mostly composed of the African States. The Philippines and specific African States share surprising similarities that qualify them as Small States under the World Bank (2023) definition. Sadly, the Philippines did not give enough attention to increase its African diplomatic base. The study mainly aims to analyze the depth of Philippine Relations with these African Small States and what diplomatic instruments these two states connect. The study found that Small States in Africa namely Gabon (4) and The Gambia (3) obtained the most bilateral agreements with the Philippines. Twenty-five (25) agreements are in the forms of Memorandum of Agreement (MOA) or Treaty. With these findings in mind, the researcher concludes that the Philippine Foreign Policy Realities should be revisited to also include Africa as one of its increased establishment of diplomatic networks as in Middle Eastern States like Saudi Arabia. Despite that, these African States only began their diplomatic approach with the Philippines with non-binding instruments (MOUs) and no follow-up documents to upgrade their ties. Having seen their similar nature and issues, it is only imperative that the Philippine Foreign Policy should give more focus on the continent of Africa as a whole as a Small State to assert its good relations with the family of nations.
Keywords: Small-Small States Cooperation; Philippine Foreign Relations; Africa; Diplomacy; Treaties